Dysregulation of X-ray repair cross-complementing 4 expression in the eutopic endometrium of women with endometriosis. Issue 2 (1st February 2022) - Bane, Kashmira; Desouza, Junita; Rojewale, Asma; Katkam, R R; Fernandes, Gwendolyn; Sawant, Raj; Dudhedia, Uddhavraj; Warty, Neeta; Chauhan, Anahita; Chaudhari, Uddhav; Gajbhiye, Rahul; Sachdeva, Geetanjali
Abstract : Recent data suggest that the DNA damage response (DDR) is altered in the eutopic endometrium (EE) of women with endometriosis and this probably ensues in response to higher DNA damage encountered by the EE in endometriosis. DDR operates in a tissue-specific manner and involves different pathways depending on the type of DNA lesions. Among these pathways, the non-homologous end joining (NHEJ) pathway plays a critical role in the repair of dsDNA breaks. The present study was undertaken to explore whether NHEJ is affected in the EE of women with endometriosis. Toward this, we focused on the X-ray repair cross-complementing 4 (XRCC4) protein, one of the core components of the NHEJ pathway. Endometrial XRCC4 protein levels in the mid-proliferative phase were found significantly ( P < 0.05) downregulated in women with endometriosis, compared to control women. Investigation of a microarray-based largest dataset in the Gene Expression Omnibus database (GSE51981) revealed a similar trend at the transcript level in the EE of women with endometriosis, compared to control women. Further in vitro studies were undertaken to explore the effects of H2 O2 -induced oxidative stress on DNA damage, as assessed by γ-H2AX and 8-hydroxy-2'-deoxyguanosine (8-OHdG) immunolocalization, and XRCC4 protein levels in endometrial stromal (hTERT immortalized human endometrial stromal cell line (ThESCs)) and epithelial (Ishikawa) cells. A significant decrease in XRCC4 protein levels and significantly higher localization of γ-H2AX and 8-OHdG were evident in ThESCs and Ishikawa cells experiencing oxidative stress. Overall, the study demonstrates that the endometrial XRCC4 expression is dysregulated in women with endometriosis and this could be due to higher oxidative stress in endometriosis.